Perancangan User Interface Platform Sosial Literasi Bookwormer dengan Metode Design Thinking - Ni Kadek Arimbi Wirasetia; I Ketut Gede Suhartana; I Komang Arya Ganda Wiguna (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2026)
Reading is a fundamental skill for intellectual growth and critical thinking development, yet Indonesia faces significant literacy challenges with only 1 out of 1000 the population reads regularly according to UNESCO data and the Indonesian National Assessment Program revealing that merely 6.06% of students possess good literacy skills. The majority of social media platforms promoting instant gratification through short-form contents have further decreasing attention spans and reading habits. This study aims to design “Bookwormer”, a social literacy platform that supports reading habits through book exploration, community engagement, and distraction-free environment. The study used Design Thinking methodology, consists of five steps: Empathize, Define, Ideate, Prototype, and Test. A prototype was developed, featuring a home page, trending books exploration, reading clubs, and personal library with reading goal statistics. Usability testing using System Usability Scale (SUS) with 20 participants yielded an average score of 81.25, indicating excellent usability. Bookwormer is able to address identified user needs and contributes in improving digital literacy culture in Indonesia.